2019
DOI: 10.1038/s41598-019-46351-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of the Anterolateral Ligament Length with the Anterior Cruciate Ligament Length and Patient’s Height: An Anatomical Study

Abstract: The aim of this study was to evaluate the anatomical characteristics of the anterolateral ligament of the knee (ALL) with the focus on potential gender differences. The ALL length and the length of the lateral collateral ligament (LCL) were taken in extension. The length of the anterior cruciate ligament (ACL) was measured at 120° flexion. We correlated the length of the ALL with the LCL and ACL with respect to potential gender differences. The ALL was significantly (p = 0.044) shorter in females (mean length:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(120 reference statements)
0
1
1
Order By: Relevance
“…The cadaveric studies are scarce which described bodyside/laterality and sex-based difference in the global population. Of note, our results for sex-based differences contrast the available reports that described a significantly shorter ALL in females 31 , 32 .…”
Section: Discussioncontrasting
confidence: 99%
“…The cadaveric studies are scarce which described bodyside/laterality and sex-based difference in the global population. Of note, our results for sex-based differences contrast the available reports that described a significantly shorter ALL in females 31 , 32 .…”
Section: Discussioncontrasting
confidence: 99%
“…The ALL runs distally, some bres attach to the lateral meniscus and the anterolateral aspect of the joint capsule (meniscal attachment), yet the majority of bres attaches to the proximal portion of the tibia (tibial attachment), dorsally to the tubercle of the iliotibial tract (4-7 mm below the articular cleft line) [82]. Ariel de Lima et al [5] showed in their literature review that the length of the ALL varies between 33 mm and 42 mm, it is signi cantly shorter in females and has a correlation with patients' height [40]. Width of the ALL ranges from 4 mm to 7 mm, its thickness varies between 1 and 2 mm and it is signi cantly thicker in males [15].…”
Section: Resultsmentioning
confidence: 99%